Prevalence and predictors of intention to be vaccinated against COVID-19 in thirteen Latin American and Caribbean countries - Caycho-Rodríguez, Tomás (2022)
The presence of a significant number of people who do not intend to be vaccinated could negatively impact efforts to control the COVID-19 pandemic. Therefore, this study sought to determine the prevalence of intention to be vaccinated against COVID-19 and associated sociodemographic and psychosocial factors in thirteen countries in Latin America and the Caribbean (LAC). A total of 5510 people from 13 LAC countries participated. Frequencies, percentages, bivariate analyses using chi-square tests, and Poisson regression analysis with robust variance were used. The countries with the highest prevalence of intention to be vaccinated were Brazil (96.94%), Cuba (89.59%), Chile (84.59%), and Mexico (78.33%). On the other hand, the countries with the lowest prevalence were El Salvador (54.01%), Paraguay (55.87%), and Uruguay (56.40%). Prevalence is also reported according to some sociodemographic and health variables. It was found that country, male sex, hours exposed to information about COVID-19, university education, living in an urban area, belief in the animal origin of the virus, perceived likelihood of contracting COVID-19, perceived severity of COVID-19, and concern about infecting others significantly predicted intention to be vaccinated in the 13 LAC countries. While most countries had a high prevalence of intention to be vaccinated, there are still subgroups that have levels of intention that may be insufficient to predict the presence of community immunity. In this sense, knowing the estimates of vaccination intention rates, as well as the associated sociodemographic and psychological factors, can be used to plan actions and interventions that will inform about the safety and benefits of vaccines, as well as strengthen trust in health authorities.